Case report: A novel combination of anomalies in a patient with 22q11.2 deletion syndrome - Byeman, Connor; Ashwath, Ravi (Frontiers in Pediatrics, 2023)
The 22q11.2 deletion is a frequently occurring genetic disorder that can manifest with various abnormalities. The range of cardiac anomalies associated with this syndrome is extensive, with conotruncal defects being the most prevalent. This case involves a patient with a unique combination of anatomical abnormalities, including crisscross pulmonary arteries, a cervical aortic arch with coarctation of the aorta, and ventricular septal defect. The patient underwent initial surgical intervention, which resulted in significant clinical improvement.